History of cochlear implantation. (November 2013) - Ramsden, Richard T
<x content-type="archive" xml:space="preserve">Abstract</x> The evolution of cochlear implantation from early experimentation with electrical stimulation of the ear in the 18th century to the sophisticated multichannel device that we now routinely implant has been remarkable. It is a tribute to the perseverance of a number of dedicated scientists in many disciplines who, in the face of serious, but ultimately unfounded, theoretical objections and ethical challenges, were eventually able to restore useful hearing to that large group of profoundly deaf adults and children, who were hitherto untreatable. The transformation in the lives of prelingually deaf children, who are now able to acquire speech and language and fulfil their full educational potential has been particularly spectacular. Cochlear implantation is the greatest advance in the field of otolaryngology in the last hundred years, and in medicine in general is one of the landmark achievements of the 20th century.